2017
DOI: 10.1007/s40268-017-0207-7
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines and Z-Drugs: An Updated Review of Major Adverse Outcomes Reported on in Epidemiologic Research

Abstract: Various adverse events resulting from, or associated with, benzodiazepine and/or Z-drug use have been extensively reported on and discussed in great detail within the biomedical literature. It is widely accepted that motor vehicle accidents and falls leading to fractures in older adults are major adverse events that have been shown to occur more frequently in users of sedative-hypnotic medication, especially of the benzodiazepine and related Z-drug variety. However, the last few years have seen increasing repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
182
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(188 citation statements)
references
References 135 publications
(153 reference statements)
3
182
0
3
Order By: Relevance
“…these medicines were developed with the aim of preventing the over-sedation and daytime sleepiness associated with benzodiazepines, and were initially believed to carry a low risk of dependence. 14 Antidepressants are not associated with a risk of dependence, are used long-term for severe depression, and can bring transformative clinical benefit. [15][16][17] However, antidepressants have become controversial, with claims that they have minimal efficacy and can be harmful.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…these medicines were developed with the aim of preventing the over-sedation and daytime sleepiness associated with benzodiazepines, and were initially believed to carry a low risk of dependence. 14 Antidepressants are not associated with a risk of dependence, are used long-term for severe depression, and can bring transformative clinical benefit. [15][16][17] However, antidepressants have become controversial, with claims that they have minimal efficacy and can be harmful.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…A review based on epidemiological research found an overwhelming degree of evidence that benzodiazepines and Z‐drugs cause fatal and nonfatal motor vehicle accidents, fractures, and cognitive dysfunction and, at least, weak evidence that these drugs cause dementia. And even if clinical doubt persists regarding the new safety accusations, such as dementia, pancreatitis, or cancer, the use of these drugs, especially in older persons, needs particular caution. Glass et al and Treves et al come to the same conclusion, namely, that for persons over 60, the benefits of sedatives and hypnotics may not justify the increased risk.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] In Germany, it is estimated that 1.2 to 1.5 million of its 82 million citizens are dependent upon tranquilizers and sleep-inducing drugs, especially older people. 8 A review based on epidemiological research 9 found an overwhelming degree of evidence that benzodiazepines and Z-drugs cause fatal and nonfatal motor vehicle accidents, fractures, and cognitive dysfunction and, at least, weak evidence that these drugs cause dementia. And even if clinical doubt persists regarding the new safety accusations, such as dementia, pancreatitis, or cancer, 9 the use of these drugs, especially in older persons, needs particular caution.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The use of BZDRs in older people is problematic because they are associated with several risks, such as sedation, dependence, falls, and fractures. 4 In general, BZDRs are approved for short-term use (less than 2-4 weeks) and not recommended for long-term use. 5 In older people, even short-term use of BZDRs poses risks due to sedation and falls resulting in fractures.…”
Section: Introductionmentioning
confidence: 99%